Distance Analysis in Badminton (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
This study aimed to determine the court area distance traveled by the badminton women’s single players. The results of the study can be the basis for further research to improve achievements in badminton. The study was conducted in Jakarta. The research was a descriptive study with survey method. The population of this study were national badminton women’s single players. The sampling technique used purposive sampling, which included the top 50 women’s single players in the world. The data collection technique used in this study was the observation of match videos taken from Youtube which were analyzed by using the kinovea software application. The data analysis technique used descriptive statistics analysis, namely data descriptions in the form of frequency distributions, graphs, and data distribution (mean, median, mode, standard deviation, and variance). The research results show that the total distance covered in one badminton game for women’s singles was 3.9 kilometers. It is expected that the Vo2max value can be standardized for badminton players by adjusting it to the badminton game category.